Combined influences of the quasi-biennial oscillation and stratospheric polar vortex on East Asian winter precipitation - Guolong Zhang; Shupeng Jiang; Boyan Chen; Xinglin Bao; Jiang Qin; Ruhua Zhang (Climate Dynamics, 2026)

Life cycle 3E (environmental–energy–economic) assessment of amine-based onboard carbon capture systems: optimal solvent screening for maritime decarbonization - Xiaojia Tang; Kehan Wang; Siyuan Xu; Shuyan Chen; Hanqiang Liu; Qingxin Wang; Can Zheng; Yangyuan Ji; Yimin Zhu (Clean Technologies and Environmental Policy, 2026)

Real-world safety profile of eravacycline compared with tigecycline, minocycline, and meropenem: a comparative pharmacovigilance analysis of the FDA Adverse Event Reporting System (FAERS) - Yan Chen; Yi Xu; Feifei Hou; Jianfeng Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

miR-584-5p suppresses Aβ1−42-induced apoptosis in Alzheimer’s disease cell model via targeting of HDAC1 - Lingyan Cheng; Pingting Gong; Xiaofeng Su; Yika Fang; Tao Wang (Acta Neurologica Belgica, 2026)

Sea Cucumber Neuropeptides: Bridging Molecular Insights Towards Aquaculture Innovations - Yingqiu Zheng; Huachen Liu; Saowaros Suwansa‐ard; Scott F. Cummins; Muyan Chen (Reviews in Aquaculture, 2026)
The sea cucumber (class Holothuroidea) holds significant commercial value due to strong global demand, especially in East and Southeast Asian markets. Overexploitation of wild stocks has thus driven aquaculture expansion; however, current culture methods remain inadequate to meet projected demand or overcome traditional practice limitations. As evolutionarily ancient endogenous bioactive molecules, neuropeptides regulate diverse physiological processes and behaviors, demonstrating great potential as eco‐friendly tools for precision sea cucumber aquaculture. Identification and functional characterization of these neuropeptides improve our understanding of their evolutionary history and facilitate their application in aquaculture practice. In this review, we summarize the diversity of known sea cucumber neuropeptides and their receptors, their engagement with downstream cellular signaling pathways, and their roles in key biological processes, including feeding and growth, reproduction, regeneration, larvae settlement and metamorphosis, and locomotion. Future research should prioritize investigating neuropeptide regulatory networks, determining their functions across developmental stages, developing large‐scale peptide production methods, and improving delivery efficiency, all of which are critical for the application of neuropeptides to achieve sustainable, eco‐friendly sea cucumber aquaculture.

Nitrogen addition and expansion of Ligularia virgaurea drive decoupling between ammonia and nitrite oxidation - Miao Zhang; Anning Zhang; Zi Yang; Wanyu Xia; Xuanchen Liu; Xiaoxuan Jiang; Xia Zhao; Hanwen Cui; Guoliang Sha; Sa Xiao; Shuyan Chen; Beat Frey (Applied Soil Ecology, 2026)

Biochar amendments enhanced organic carbon pool stability in soil aggregates by regulating soil carbon functional microbes - Xiyu Xiang; Yan Chen; Yanyan Lu; Jiahui Chen; Haiyang Zhang; Huiying Zhao; Shuchen Sun; Sheng Zhai; Xiaofei Tian (Applied Soil Ecology, 2026)

Effect of microbe-mediated allelochemicals derived from soil of a plant species on two co-occurring native plant species - Jiajia Wang; Kun Liu; Carol C. Baskin; Ziyang Liu; Hanwen Cui; Jingwei Chen; Yajun Wang; Hongxian Song; Zi Yang; Anning Zhang; Lizhe An; Sa Xiao; et al. (Applied Soil Ecology, 2025)

Shrub removal suppresses the effects of warming on nematode communities in an alpine grassy ecosystem - Zi Yang; Jingwei Chen; Jiajia Wang; Ziyang Liu; Lihua Meng; Hanwen Cui; Sa Xiao; Anning Zhang; Kun Liu; Lizhe An; Shuyan Chen; Uffe N. Nielsen (Applied Soil Ecology, 2025)

Cell Death in Crustacean Immune Defense - Zeyan Chen; Muhammad Tayyab; Defu Yao; Jude Juventus Aweya; Zhihong Zheng; Xianliang Zhao; Zhongyang Lin; Yueling Zhang (Reviews in Aquaculture, 2025)
Cell death mechanisms in crustaceans are a complex interplay of processes essential for maintaining cellular homeostasis and immune defense. Modes of cell death like apoptosis, necroptosis, and necrosis are well‐documented in crustaceans, serving crucial roles in removing damaged or infected cells. Unlike in other organisms, crustaceans likely lack pyroptosis, a type of programmed cell death associated with innate immunity and inflammation, because they do not possess the gasdermin genes essential for this process. Recently, NETosis and ferroptosis have emerged as significant mechanisms in pathogen defense. NETosis, involving the release of DNA fibers and antimicrobial proteins, helps trap and neutralize pathogens, while ferroptosis, an iron‐dependent form of cell death, contributes to lipid peroxidation and immune responses. Cuproptosis, although not yet studied in the context of crustacean immunity, shows potential crosstalk with ferroptosis, particularly in the regulation of metal ion homeostasis, oxidative stress, and cellular metabolism. Understanding these mechanisms offers promising applications in aquaculture, such as developing targeted immune modulators and enhancing disease resistance in economically important crustacean species.

The regulation of shrimp metabolism by the white spot syndrome virus (WSSV) - Ramya Kumar; Jiun‐Yan Huang; Yen‐Siong Ng; Cong‐Yan Chen; Han‐Ching Wang (Reviews in Aquaculture, 2022)
For more than three decades, infectious diseases have been one of the major causes of economic losses in the global shrimp industry. One of the deadliest of the shrimp pathogens is white spot syndrome virus (WSSV), which causes mass mortality in farmed shrimp. Various aspects of WSSV pathogenicity have been studied, but in this review, we will focus only on one of them, namely metabolic reprogramming. WSSV’s modulation of host metabolism affects glycolysis, the tricarboxylic acid (TCA) cycle, glutaminolysis and lipid metabolism. Several signaling pathways are involved in this regulation, including JAK‐STAT, PI3K‐AKT‐mTOR, MAPK and Ras‐Raf‐MEK, with the PI3K‐Akt‐mTOR pathway in particular playing a critical role in activating the WSSV‐induced Warburg effect. Taken together, these changes benefit the virus by facilitating WSSV replication. In this review, we summarize current knowledge regarding the metabolism‐related aspects of WSSV pathogenesis, and discuss the mechanisms by which this virus reprograms its host's metabolic pathways. A deeper understanding of these pathways, key metabolic enzymes and signaling mechanisms is potentially important for the development of effective anti‐WSSV strategies.